Pengaruh Budaya Organisasi, Gaya Kepemimpinan Dan Kepercayaan Diri Terhadap Komitmen Kerja Pegawai Dinas Pendidikan Dan Kebudayaan Kota Padang - Nova Gusmery; Febsri Susanti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out and analyze the influence of organizational culture, leadership style, and self-confidence on the work commitment Employees of Department Education and Culture Padang City. This type of research is quantitative research. This study uses primary data obtained through distributing questionnaires to Employees of Department Education and Culture Padang City. The total population of this study was 117 people. Sampling in this study using total sampling technique. The number of samples in this study were 117 respondents. The data analysis technique used is multiple linear regression and t-statistic test. The research results show that, Organizational culture has a significant effect on the work commitment Employees of Department Education and Culture Padang City. Leadership style has a significant effect on the work commitment Employees of Department Education and Culture Padang City. Self-confidence variable has a significant effect on the work commitment Employees of Department Education and Culture Padang City. The work commitment is influenced by organizational culture, leadership style and self-confidence of 75.5%. While the remaining 24.5% is influenced by other factors not examined in this study, such as work environment, work motivation, work discipline, personality and so on.